Solvent-free reduction of carboxylic acids to alcohols with NaBH4 promoted by 2,4,6-trichloro-1,3,5-triazine and PPh3 in the presence of K2CO3 - Subin Jaita (2018)
© the Partner Organisations 2014. A simple, rapid, and eco-friendly method for NaBH 4 reduction of carboxylic acids to alcohols under solvent-free conditions was developed using a combination of 2,4,6-trichloro-1,3,5-triazine (TCT) with a catalytic amount of triphenylphosphine as an acid activator. With the 1 : 0.2 : 1.5 : 2 mole ratio of TCT : PPh 3 : K 2 CO 3 : NaBH 4 , carboxylic acids including aromatic acids, aliphatic acids, and N-protected α-amino acids (Fmoc, Z) could readily undergo reduction to give the corresponding alcohols in good to excellent yields within 10 min.